2003
DOI: 10.18474/0749-8004-38.3.398
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant and Toxic Effects of a Neem (Azadirachta indica A. Juss)-Based Formulation Neemix® Against Nezara viridula (L.) (Hemiptera: Pentatomidae)

Abstract: The antifeedant activity of Neemix 4.5 EC, a commercial formulation of azadirachtin from the neem tree (Azadirachta indica A. Juss), was tested against adult Nezara viridula (L.) in the laboratory using a cowpea pod-dip method. A toxicity assay was conducted by dipping fourth-instar nymphs. Feeding by adults was significantly reduced in treated pods compared with controls, based on counts of salivary deposits on pod surfaces, inside pod walls and on seeds. The antifeedant effect of azadirachtin was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Their presence in both the unsprayed plots and those of the botanical insecticide plots is an indication of the relative harmlessness of this type of insecticide on them. This result is in agreement with the work of [18] whose work found no effect of neem on the predatory activities of Coccinellidae spp. on N. viridula eggs and suggested neem as an important component of IPM on this particular insect pest.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Their presence in both the unsprayed plots and those of the botanical insecticide plots is an indication of the relative harmlessness of this type of insecticide on them. This result is in agreement with the work of [18] whose work found no effect of neem on the predatory activities of Coccinellidae spp. on N. viridula eggs and suggested neem as an important component of IPM on this particular insect pest.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of this study is in agreement with those of [24] who reported 20% increase in asilids abundance in organic fields compared to the conventional farming fields (which use chemical pesticides). Apart from repelling both adult and larvae, disrupting their development processes including sterility, nke is known to affect insect pests in various other ways such as causing confusion (immobilization) in the behaviour of adults [18]. The effect of this is to enhance predation as the prey becomes easier to capture.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanism of action of the aqueous extracts on the insect, important to would be understand. It is also important to search insecticide molecules to generate new synthetic products and to obtain natural insecticides for direct use, to produce commercial formulation (Abudulai et al, 2003) or that can be expressed in plants acting as molecular defenses against herbivores insects (Peumans and Van Damme, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…There is, therefore, the need for novel and alternative pest control strategies that are cheaper to use and also less detrimental to the environment. Extracts from the neem tree, Azardirachta indica A Juss have deterrent and insecticidal properties against over 400 insect pests and could be used for pest control in cabbage (Schmutterer, 1985;Abudulai et al, 2004). The extracts act as contact and stomach poisons, and disrupt the development of eggs, larvae, pupae or prevent moulting of larvae or nymphs (Singh, 1994;.…”
Section: Introductionmentioning
confidence: 99%
“…The neem tree is ubiquitous in Ghana and can therefore be a cheap source of insecticides for pest control in cabbage and other crops. Moreover, neem is non-toxic to mammals and also benign to nontarget organisms (Ascher, 1993;Abudulai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%